Still Alice a novel - Genova, Lisa (New York Gallery Books, 2014)
Alice Howland -- Harvard professor, gifted researcher, and lecturer, wife, and mother of three grown children -- sets out for a run and soon realizes she has no idea how to find her way home. She has taken the route for years, but nothing looks familiar. She is utterly lost. Medical consults reveal early-onset Alzheimer's. Alice slowly but inevitably loses memory and connection with reality, as told from her perspective. She gradually loses the ability to follow a conversational thread, the story line of a book, or to recall information she heard just moments before. Genova shows the disease progression through the reactions of others, as Alice does, so readers feel what she feels: a slowly building terror.
Includes readers club guide and first two chapters of Inside the O'Briens (2015).
102270
Keywords: Alzheimer's disease; Alzheimer's disease -- Patients -- Family relationships; Women college teachers; Women linguists; Domestic fiction